Does Corporate Ownership Enforce Sustainable Development? An Empirical Study on Korean Companies - Youngsoo Ra (Asian Academy of Management Journal of Accounting and Finance, 2021)
This study examined Korean companies on whether ownership affects corporate social responsibility performance (CSP) to influence on the corporate financial performance (CFP). According to the results, ownership has causational relationship with financial performance of firms varies upon proxy of CFP. Ownership and CFP demonstrates reverse-U type with ROA but U-type with market to book ratio (MB ratio). Second, ownership and CSP does not prove to have any causality. Partly, ownership shows negative effects on corporate governance. Finally, CSP does not affect profit (ROA) but improve the market value. For the moment, CSP is not an active factor to find out that high proportion of the companies in the sample during the research period were credited low CSP. Most of the companies with high credits on CSP are efficient and stable profit earning companies which leave room to considerthe slack-resource theory.